IMPLEMENTASI EKSPERIMEN DALAM PEMBELAJARAN IPA SMP DI KECAMATAN LEITIMUR SELATAN DAN LEIHITU - Limba, Anatasija; Batlolone, Agustina; Henaulu, Ramla; Sia, Jafar; Kalauw, Dini Hardiyanti (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Evidence and real experience in learning through experimental activities in class have not been fully implemented because science learning is still carried out with an expositoric approach as so far often done by teachers. Pattimura University through a teaching assistance program held in 2022 was also carried out at SMP PGRI 2 Ambon, SMPN 8 Ambon, SMPN 3 Central Maluku and SMPN 37 Central Maluku by implementing experiments in learning the concepts of Electricity, Magnetism, Soil and life sustainability and Biotechnology. In this activity, lecturers act as teachers who teach students, while science subject teachers are in the classroom and carry out the process of observing the implementation of learning to learn the experimental process carried out to later be applied in the teaching and learning process. This activity turned out to provide experience for science teachers in preparing themselves for the learning process in their respective classes. In addition, this activity also increases student activities and learning outcomes and increases student mobility in learning science